East Asian visions: perspectives on economic development - "Gill ,Indermit (ed.)" (Washington D.C, 2007)
This volume brings together the views of noted East Asian policymakers and academics on development prospects in the region. The topics they write about include governance, inequality, corruption, provision of public goods, China's 'peaceful rise', rural-urban disparities, domestic trade networks, industrial and financial sector networks, and the consequences of regional financial integration. The contributor list includes: Tommy Koh, Kishore Mahbubani, Andrew Sheng, Roberto de Ocampo, Haruhiko Kuroda, Mari Pangestu, Toyoo Gyohten.
Keywords: East Asia-Economic integration